2011
DOI: 10.1186/1471-2334-11-63
|View full text |Cite
|
Sign up to set email alerts
|

Anal infections with concomitant Chlamydia trachomatisgenotypes among men who have sex with men in Amsterdam, the Netherlands

Abstract: BackgroundLymphogranuloma venereum (LGV) proctitis is caused by Chlamydia trachomatis (Ct) genotype L and is endemic among men who have sex with men (MSM) in western society. Genotype L infections need to be distinguished from non-LGV (genotypes A-K) Ct infections since they require prolonged antibiotic treatment. For this purpose, an in-house developed pmpH based LGV polymerase chain reaction (PCR) test is used at the Amsterdam STI outpatient clinic. We investigated retrospectively the anal Ct genotype distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 33 publications
6
34
0
5
Order By: Relevance
“…In this study, genovar G/Ga was found to be endemic among male patients from southern China, which is consistent with the C. trachomatis genovar distribution patterns found in populations of men who have sex with men (MSM) in China (8), Australia (17), and the Netherlands (18). An earlier study has shown that polymorphisms of the open reading frames of the ompA gene were strongly associated with rectal tropism in serovar G isolates (19).…”
supporting
confidence: 66%
“…In this study, genovar G/Ga was found to be endemic among male patients from southern China, which is consistent with the C. trachomatis genovar distribution patterns found in populations of men who have sex with men (MSM) in China (8), Australia (17), and the Netherlands (18). An earlier study has shown that polymorphisms of the open reading frames of the ompA gene were strongly associated with rectal tropism in serovar G isolates (19).…”
supporting
confidence: 66%
“…From the Netherlands, 107 rectal swab samples were collected at the Public Health Service in Amsterdam in 2008 and 2009. The Dutch samples were previously described by Quint et al (29). From the United States, 145 rectal swab samples from MSM were collected at Johns Hopkins University in Baltimore, MD, in 2010 and 2011, and samples from across the United States (Boston, New York, Washington, DC, Atlanta, San Francisco, and Los Angeles) were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is now referred to as genovar determination. Genovars E, D, and F are highly prevalent in heterosexual populations worldwide (23,26,31,33), while genovars G, D, and J predominate in MSM populations (2,20,22,29,32). Since 2003, clonal outbreaks of invasive strains of C. trachomatis causing lymphogranuloma venereum (LGV) with severe proctitis have been described among MSM in Europe, often in combination with HIV and other sexually transmitted diseases.…”
mentioning
confidence: 99%
“…Mixed infections are also prevalent in populations with a high propensity for acquiring STDs (108,111,(130)(131)(132)(133). Moreover, opportunities for intrabiovar recombination events are abundant in coinfections of the rectal mucosa with LGV and noninvasive urogenital strains, such as those from serotypes D, G, J, E, F, and K, that also infect the rectum (134)(135)(136)(137)(138)(139). Alternatively, several reports suggest that chlamydial species might persist in humans as commensals of the lower gastrointestinal tract (reviewed in reference 140), which could provide fertile grounds for inter-and intrabiovar exchange of DNA.…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%